Modul Remedial Biologi Materi Keanekaragaman Hayati - Tri Murnilawati; Syamsurizal Syamsurizal; Bambang Hariyadi (Universitas Jambi, 2015)
The aim of this development is to create a learning module that can increase students' motivation and facilitate remedial students to perform learning. The module is created contains instructions for using the module, perform remedial instructions for students, subject matter, competency testing per learning activities, feedback, answer keys, a summary of the material to the glossary contains terms used in the learning module. The model used in the design development using ADDIE model of instructional design, outline development model consists of 5 stages are: analysis, design, development, implementation and evaluation. The data obtained in this study is qualitative data obtained from the comments and suggestions validator (materials and expert design expert module) and peer comments, while the quantitative data obtained from the students' response to the learning modules, before remedial value and value increase learning achievement after using remedial module. The test is done in small groups of 6 students and a large group of 33 students. Based on the results of the validation and field trials have shown that the media developed is feasible and can be applied to students of class X results in research trials shows that students can respond with a good media applied.